2016
DOI: 10.1016/j.jtcme.2014.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate-containing beetroot enhances myocyte metabolism and mitochondrial content

Abstract: Beetroot (甜菜 tián cài) juice consumption is of current interest for improving aerobic performance by acting as a vasodilator and possibly through alterations in skeletal muscle metabolism and physiology. This work explored the effects of a commercially available beetroot supplement on metabolism, gene expression, and mitochondrial content in cultured myocytes. C2C12 myocytes were treated with various concentrations of the beetroot supplement for various durations. Glycolytic metabolism and oxidative metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…NO activates AMPK‐α, an energy‐sensing enzyme activated in response to cellular stress and by increased intracellular cGMP . Beetroot juice increased basal oxidative metabolism and glucose uptake in C2C12 myocytes with elevated metabolic gene expression including peroxisome proliferator‐activated receptor gamma coactivator‐1 alpha (PGC‐1α), nuclear respiratory factor 1, mitochondrial transcription factor A, and glucose transporter 4, leading to increased mitochondrial biogenesis . In our study, both beetroot and sodium nitrate interventions improved glucose tolerance independent of changes in body weight, similar to a previous study with sodium nitrate treatment in obese ZSF1 rats suggesting that nitrate regulated glucose uptake through SIRT3 (sirtuin 3)‐AMPK activation in skeletal muscle .…”
Section: Discussionsupporting
confidence: 89%
“…NO activates AMPK‐α, an energy‐sensing enzyme activated in response to cellular stress and by increased intracellular cGMP . Beetroot juice increased basal oxidative metabolism and glucose uptake in C2C12 myocytes with elevated metabolic gene expression including peroxisome proliferator‐activated receptor gamma coactivator‐1 alpha (PGC‐1α), nuclear respiratory factor 1, mitochondrial transcription factor A, and glucose transporter 4, leading to increased mitochondrial biogenesis . In our study, both beetroot and sodium nitrate interventions improved glucose tolerance independent of changes in body weight, similar to a previous study with sodium nitrate treatment in obese ZSF1 rats suggesting that nitrate regulated glucose uptake through SIRT3 (sirtuin 3)‐AMPK activation in skeletal muscle .…”
Section: Discussionsupporting
confidence: 89%
“…In a meta-analysis examining the effect of nitrate supplementation on exercise performance in healthy individuals, Hoon et al 15 reported, “Qualitative analysis suggested that performance benefits are more often observed in inactive to recreationally active individuals and when a chronic loading of NO 3 - over several days is undertaken.” Given the number of studies published recently in addition to our findings, it is becoming evident that the benefits of dietary NO 3 - may be limited to those individuals who have not already received the benefit of chronic physiological adaptation to aerobic exercise training 15 , 16 . Dietary nitrate has been implicated in improved mitochondrial efficiency, which may provide some indication of the mechanism through which some individuals receive benefit 25 27 . Although speculative, dietary nitrate may alter blood flow distribution including vasodilation of non-working muscle vascular beds as dietary nitrate does not prioritize a site-specific vasodilation to muscles engaged in exercise.…”
Section: Discussionmentioning
confidence: 99%
“…These in vivo studies confirm that NO indeed affects skeletal muscle bioenergetics, but they do not disclose the underlying molecular mechanism. In vitro experiments with C2C12 myocytes show that beetroot juice provokes mitochondrial biogenesis and modestly increases basal cellular respiration without affecting respiratory capacity and proton leak (Vaughan et al, 2014 ). These observations indicate improved mitochondrial coupling efficiency as beetroot juice has increased the proportion of total O 2 consumption coupled to ATP synthesis.…”
Section: Skeletal Muscle Bioenergeticsmentioning
confidence: 99%